2017
DOI: 10.1103/physrevb.95.165131
|View full text |Cite
|
Sign up to set email alerts
|

Haldane phase on the sawtooth lattice: Edge states, entanglement spectrum, and the flat band

Abstract: International audienceUsing density matrix renormalization group numerical calculations, we study the phase diagram of the half filled Bose-Hubbard system in the sawtooth lattice with strong frustration in the kinetic energy term. We focus in particular on values of the hopping terms which produce a flat band and show that, in the presence of contact and near neighbor repulsion, three phases exist: Mott insulator (MI), charge density wave (CDW), and the topological Haldane insulating (HI) phase which displays … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…They appear for a sufficiently strong repulsive interaction as dynamically stable excited states. More recently, pair formation was proposed in the ground state of the bosonic Hubbard model in some special onedimensional lattice structures [29,32,25,27,10,6]. The pair formation occurring here is a collective effect and is caused by the interplay between the repulsive interaction and the movement of the particles in these lattice structures.…”
Section: Introductionmentioning
confidence: 93%
“…They appear for a sufficiently strong repulsive interaction as dynamically stable excited states. More recently, pair formation was proposed in the ground state of the bosonic Hubbard model in some special onedimensional lattice structures [29,32,25,27,10,6]. The pair formation occurring here is a collective effect and is caused by the interplay between the repulsive interaction and the movement of the particles in these lattice structures.…”
Section: Introductionmentioning
confidence: 93%
“…For certain systems like the spin-1 XXZ model, the topological order is also captured by an even degeneracy of the entanglement spectrum (ES) [28]. From the other side, in different models, like for instance the AKLT [29] or exotic bosonic Hamiltonians [30], the ES does not present even degeneracy but the topological order is assured by the presence of edge modes and finite SOPs. We checked that this happens also in our case where the ES of t < 1 deformed Motzkin chains does not display any degeneracy.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In the sawtooth lattice, it was found that doping above the critical density leads to a phase where the peak of the momentum distribution is at nonzero momentum [13], while doping the kagome lattice leads to a supersolid phase [13]. Adding longer range interactions between the bosons on the sawtooth lattice uncovers topological effects such as the Haldane insulator phase and edge states in open systems [19]. Bosons were also studied on the flat band Creutz lattice ( Fig.…”
Section: Introductionmentioning
confidence: 99%